Volumetric efficiency modeling of a four stroke IC engine - Yin, Shumei, author; Kirkpatrick, Allan T., advisor; Cheney, Margaret, committee member; Gao, Xinfeng, committee member (Colorado State University. Libraries, 2017)
Volumetric efficiency, one of the most important engine performance parameters, is influenced by several engine parameters such as valve timing, valve lift, intake and exhaust runner length, and intake and exhaust pressure. To explore how these parameters impact volumetric efficiency, a 1D unsteady thermal fluid analysis is performed to determine the instantaneous cylinder pressure and the mass flow rate through the intake and exhaust valves during the intake and exhaust processes. In addition to a MATLAB implementation, a GT-Power model is also developed for validation. A synthetic intake pressure pulse is then added to the model to explore the engine intake tuning effect. The results predict a volumetric efficiency increase by about $9\%$ when this pulse enters the cylinder near bottom dead center (BDC). The prediction is consistent with an acoustic model predicting that the maximum volumetric efficiency is reached when the natural frequency of the intake system equals the frequency of the intake process. The GT-Power model is also used to validate the relationship between the engine speed and intake runner length for optimal volumetric efficiency. The results from GT-Power do not agree with the Helmholtz model very well. Finally, the effect of the intake valve timing, valve lift and intake and exhaust pressure on volumetric efficiency are also determined.
Keywords: MATLAB; volumetric efficiency; modeling; GT-Power